The Shigella flexneri virulence factor apyrase is released inside eukaryotic cells to hijack host cell fate - Lisa Perruzza; Carlo Zagaglia; Laura Vitiello; Meysam Sarshar; Francesco Strati; Martina Pasqua; Fabio Grassi; Mauro Nicoletti; Anna Teresa Palamara; Cecilia Ambrosi; Daniela Scribano (Microbiology Spectrum, 2023)
ABSTRACT Intestinal epithelial cells represent the first line of defense from invading enteric pathogens. During the course of infection, pro-inflammatory programmed cell death is an effective way to eliminate invading microbes and to create a localized inflammatory environment. On the other hand, pathogens evolved countless strategies to overcome cell death and to keep the host alive ensuring their spread. It was previously shown that Shigella flexneri apyrase interacts with OmpA to contribute to a proper polar exposition of IcsA, which mediates actin-based motility. However, apyrase is also an ATP-diphosphohydrolase whose catalytic activity function has not been elucidated yet. Herein, we demonstrated that apyrase contributes to the manipulation of host cell fate by S. flexneri since it is released within the host cell cytoplasm during infection to degrade intracellular ATP. Thus, apyrase contributes to prevent caspase-1 activation, thereby downregulating the activation of pyroptosis in infected cells. Overall, apyrase is involved in the modulation of host cell survival and dampens the inflammatory response. IMPORTANCE In this paper, we demonstrated that apyrase is released within the host cell cytoplasm during infection to target the intracellular ATP pool. By degrading intracellular ATP, apyrase contributes to prevent caspases activation, thereby inhibiting the activation of pyroptosis in infected cells. Our results show, for the first time, that apyrase is involved in the modulation of host cell survival, thereby aiding this pathogen to dampen the inflammatory response. This work adds a further piece to the puzzle of Shigella pathogenesis. Due to its increased spread worldwide, prevention and controlling strategies are urgently needed. Overall, this study highlighted apyrase as a suitable target for an anti-virulence therapy to tackle this pathogen.